Предмет: Алгебра,
автор: ilya583
Решить уравнение
x²(x+3)=4(x+3)
Ответы
Автор ответа:
0
x^2(x+3) = 4(x+3)
x^2*x+3x^2 = 4x+12
x^3+3x^2-4x-12 = 0
x^2(x+3)-4(x+3) = 0
(x+3)(x^2-4) = 0
x = -3
x = 2
x = -2
x^2*x+3x^2 = 4x+12
x^3+3x^2-4x-12 = 0
x^2(x+3)-4(x+3) = 0
(x+3)(x^2-4) = 0
x = -3
x = 2
x = -2
Похожие вопросы
Предмет: Физкультура и спорт,
автор: povodovakate
Предмет: Алгебра,
автор: disidodsi
Предмет: Русский язык,
автор: Jade5krasota
Предмет: Математика,
автор: tasokolenko
Предмет: Химия,
автор: alinahoran1509